2018
DOI: 10.3390/metabo8020038
|View full text |Cite
|
Sign up to set email alerts
|

Untargeted Metabolomic Analysis of Rat Neuroblastoma Cells as a Model System to Study the Biochemical Effects of the Acute Administration of Methamphetamine

Abstract: Methamphetamine is an illicit psychostimulant drug that is linked to a number of diseases of the nervous system. The downstream biochemical effects of its primary mechanisms are not well understood, and the objective of this study was to investigate whether untargeted metabolomic analysis of an in vitro model could generate data relevant to what is already known about this drug. Rat B50 neuroblastoma cells were treated with 1 mM methamphetamine for 48 h, and both intracellular and extracellular metabolites wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Earlier studies demonstrated that METH administration could perturb amino acid metabolism. 13 By using metabolomic analysis of rat serum 13 and neuroblastoma cells, 41 amino acids were the most notable metabolites affected by METH, including glutamate, aspartate, methionine, phenylalanine and serine. Summarizing the results of METH associated metabolomics profiling, 13 amino acids were decreased in the serum of rat model except glutamate, 12 but glutamine, ornithine, histidine, asparagine, glutamate, taurine, and citrulline were increased in the serum of human METH abusers.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies demonstrated that METH administration could perturb amino acid metabolism. 13 By using metabolomic analysis of rat serum 13 and neuroblastoma cells, 41 amino acids were the most notable metabolites affected by METH, including glutamate, aspartate, methionine, phenylalanine and serine. Summarizing the results of METH associated metabolomics profiling, 13 amino acids were decreased in the serum of rat model except glutamate, 12 but glutamine, ornithine, histidine, asparagine, glutamate, taurine, and citrulline were increased in the serum of human METH abusers.…”
Section: Discussionmentioning
confidence: 99%
“…This study also found that the expression of the DLG2 gene was up-regulated in WMA subjects. There was a long-term cognitive impairment in methamphetamine addicted populations ( Crocker et al, 2014 ), as well as dysfunction of the glutamate system ( Maker et al, 2018 ). The DLG2 gene may play an important role in the development, plasticity, and stability of glutamatergic synapses and may further affect the cognitive function of WMA patients.…”
Section: Discussionmentioning
confidence: 99%
“…A broad diversity of cellular models, including tumorigenic and nontumorigenic immortalized cell lines [ 36 , 37 , 38 ], primary cells obtained from different tissues [ 39 , 40 ], and stem cells [ 41 , 42 ] have been used in in vitro metabolomic studies, access to which is facilitated through cell culture biobanks, such as the American Type Culture Centre (ATCC, ) [ 36 ]. Immortalized cell lines offer several advantages over primary and stem cells, as they are economical and highly available, are easy to handle, can be kept in culture for longer periods of time, provide an unlimited and pure population of cells with a stable phenotype that guarantee reproducible results, and circumvent ethical concerns associated with the use of animal and/or human samples [ 29 , 31 , 43 ].…”
Section: Metabolomics Workflowmentioning
confidence: 99%